Pendermaan organ di Malaysia: dari sudut agama dan budaya / Siti Rohana Daud ... [et al.] - Daud, Siti Rohana; Mukapit, Mukhiffun; Suhaime, Intan Liana; Ahmad, Khaizie Sazimah; Jogeran, Jumaelya; Sehat, Nani Shuhada (2018)
Organ donation is an issue that is very much discussed nowadays. Religion and culture will be major factors in the discussion of the issue. This paper will explore how the two factors that can be a hinder or motivator on the number of organ donors in Malaysia. This paper also to identify the strategies developed by the Ministry of Health and several other parties to attract more pledger and emphasize religious and cultural factors in the campaign. The findings from local and overseas studies are examined to see the extent of the effectiveness of the strategies implemented based on religious and cultural factors. The increase in donor organ donation shows that the community is aware and understands the need for organ donation. Religion and culture are no longer a barrier, but it is a motivating factor. Furthermore, the delivery of information and effective strategies help to awareness of organ donation among Malaysians.